Pertanggungjawaban Pidana dan Penanggulangan Tindak Pidana Pencabulan terhadap anak - Samai, Butria; Toule, Elsa Rina Maya; Hattu, Jacob (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: This study discusses the legal regulation of the crime of molestation of children and the criminal liability of the perpetrators of the crime of molestation against children in the case.Purposes of the Research: To analyze and discuss legal regulations regarding criminal acts of molestation against children and explain criminal responsibility for perpetrators of criminal acts of molestation against children in Halong Baru, Baguala District, Ambon City.Methods of the Research: The research method used is normative juridical research. This research uses three problem approaches, namely the statutory approach, the conceptual approach and the case approach. The data sources obtained are primary legal materials and secondary legal materials. The technique for collecting legal materials uses the literature study method. All data in this study were analyzed qualitatively.Results of the Research: The results of this research show that, criminal responsibility for perpetrators of criminal acts of sexual abuse against children is a further consequence that must be accepted or borne by the defendant. During the trial process, the defendant was in good physical and mental health and no reason was found to erase the crime, in this case either a justifying reason or a forgiving reason, so that the defendant was able to take responsibility for the actions he committed. The efforts made to overcome acts of sexual abuse against children are carried out with preventive and repressive efforts by law enforcement and other institutions.